Uji Kapasitas Dukung Pondasi Tiang Kelompok Ujung Terbuka Dengan Variasi Pengaruh Spasi Serta Panjang Tiang - M. Yusuf Agustamar; Soewignjo Agus Nugroho; Syawal Satibi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
In planning a good structure, it is necessary to consider a geographical factor where the building is built. Soil conditions that generally exist in Indonesia’s coastal is soft soil. As well as, that the most widely used foundation type is the pile foundation. The pile foundation is used to support a structure when a good soil lies at a relatively deep and also if the foundation of the building lies on a fairly high embankment. A number of piles used as pile foundation in one pilecap, where the piles working together to support building. Hence the study of pile foundation needs to be done. One of the studies is modeling of pile in pile grup foundation to find out the bearing capacity of the pile group on sand. Notably, Variation of spacing and length of the pile is determined for this study.The research was done by direct test model on pile foundatio with variation of length 40 cm, 30 cm, and 20 cm and spacing variation with 2.5D, 3D, and 5D also. In brief, the result test in 40 cm lenght pile with spacing 2,5D has the greatest capacity. Obviously the results of the interpretation with the Chin method found a pile with a length of 40 cm and 2.5D pile spacing is the pile with the largest Qult of 2.232 kN followed by a 30 cm long pile with a space 2.5D, as well as the interpretation of Terzhagi and Peck method, the pile with long 40 cm and 2.5D spaces have the largest Qult that is 1.665 kN. To summarize, based on the results of the research can be concluded that the more tight spaced pile then Qult pile will be bigger, and longer pile on the foundation model then Qult also getting bigger.Keywords: Loose sand, Foundation, Pile group, Bearing capacity.